2010
DOI: 10.1111/j.1439-0396.2008.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an organic acid blend and phytase added to a rapeseed cake-containing diet on performance, intestinal morphology, caecal microflora activity and thyroid status of broiler chickens

Abstract: The experiment was carried out on 96 female broilers, allocated to eight groups of 12 birds kept in individual cages. Two basal wheat- and soyabean meal-based diets containing 150 g/kg of rapeseed expeller cake were formulated, differing in the level of P: 7.1 g/kg in diet H or 5.9 g/kg in diet L. Rapeseed cake supplied 3.15 micromol alkenyl glucosinolates per gram of diet. The eight treatments were: basal diets only, basal diets + phytase (1000 U/kg), basal diets + organic acid blend (OA, 6 g/kg), or basal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 22 publications
6
35
0
1
Order By: Relevance
“…Phytase supplementation increased the SCFA concentration in caecal digesta, decreased liver weight and did not affect thyroid weight. In our former studies we also found an increase of SCFA concentration in caecal digesta after supplementation of a rapeseed cake-containing diet with phytase, but this was accompanied by an increase of thyroid weight in broilers (Smulikowska et al, 2006(Smulikowska et al, , 2010. It is worth noting that the glucosinolate levels in press cakes in the former studies were higher.…”
Section: Discussionmentioning
confidence: 68%
“…Phytase supplementation increased the SCFA concentration in caecal digesta, decreased liver weight and did not affect thyroid weight. In our former studies we also found an increase of SCFA concentration in caecal digesta after supplementation of a rapeseed cake-containing diet with phytase, but this was accompanied by an increase of thyroid weight in broilers (Smulikowska et al, 2006(Smulikowska et al, , 2010. It is worth noting that the glucosinolate levels in press cakes in the former studies were higher.…”
Section: Discussionmentioning
confidence: 68%
“…Although there are no performance differences between the treatments, the association of phytogenic additves and organic acids can be used in order to improve performance. Additive and/or synergistic effect was observed with the combinations of probiotics and acidifiers (Khosravi et al, 2010), sanguinarine and organic acids (Vieira et al, 2008), essential oils and enzymes (Basmacioğlu Malayoğlu et al, 2010), acidifiers and enzymes (Smulikowska et al, 2010) and phytogenics and probiotics, improving the immune system of the birds (Li et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Clostridium thrives on mucin, and a reduction in mucin levels could correspond to a reduction in C. perfringens and the occurrence of NE (74) . Increased caecal acetate was reported in broiler chickens fed phytase, an indication of microbial activity modulation (75) . In pigs, supplemental phytase was observed to increase Clostridium group in the ileum without changing total bacterial numbers (76) and Bifidobacterium and Clostridium numbers (77) in the ileum.…”
Section: Phytasementioning
confidence: 99%